Potent SARS-CoV-2 binding and neutralization through maturation of iconic SARS-CoV-1 antibodies. Issue 1 (1st January 2021) - Rouet, Romain; Mazigi, Ohan; Walker, Gregory J.; Langley, David B.; Sobti, Meghna; Schofield, Peter; Lenthall, Helen; Jackson, Jennifer; Ubiparipovic, Stephanie; Henry, Jake Y.; Abayasingam, Arunasingam; Burnett, Deborah; et al.
ABSTRACT: Antibodies against coronavirus spike protein potently protect against infection and disease, but whether such protection can be extended to variant coronaviruses is unclear. This is exemplified by a set of iconic and well-characterized monoclonal antibodies developed after the 2003 SARS outbreak, including mAbs m396, CR3022, CR3014 and 80R, which potently neutralize SARS-CoV-1, but not SARS-CoV-2. Here, we explore antibody engineering strategies to change and broaden their specificity, enabling nanomolar binding and potent neutralization of SARS-CoV-2. Intriguingly, while many of the matured clones maintained specificity of the parental antibody, new specificities were also observed, which was further confirmed by X-ray crystallography and cryo-electron microscopy, indicating that a limited set of VH antibody domains can give rise to variants targeting diverse epitopes, when paired with a diverse VL repertoire. Our findings open up over 15 years of antibody development efforts against SARS-CoV-1 to the SARS-CoV-2 field and outline general principles for the maturation of antibody specificity against emerging viruses.